KONTRADIKSINILAI PENDIDIKAN ANTIKORUPSI ANTARANOVEL NEGERI PARA BEDEBAHDAN SI ANAK PINTAR KARYA TERE LIYE - Sigit Arif Bowo (p-ISSN 2356-0576, 2019)
Abstract: this study aims to describe the contradiction in the value of honesty anti-corruption education between the novel Negeri Para Bedebah and Si AnakPintar by TereLiye. This research is a qualitative description. Data collection techniques using the technique of reading and note taking.Data analysis techniques using theory triangulation.Based on the results of the analysis shows that in the novel Si AnakPintarthere are honesty anti-corruption education values which include: (1) not stealing, (2) not falsifying documents, (3) implementing policies based on truth, (4) competing fairly, and (5) not embezzled funds. While in the novel Negeri Para Bedebah there are contradictions in the value of honesty anti-corruption education which include: (1) not implementing truth-based policies, (2) collusion, (3) bribery, (4) falsifying documents, and (5) committing fraud. These findings are relevant as teaching materials for anti-corruption education. Keywords: values, education, anti-corruption, novels, sociology of literature   Abstrak: penelitian ini bertujuan untuk mendeksripsikan kontradiksi nilai pendidikan antikorupsi kejujuran antara novel Negeri Para Bedebah dan Si Anak Pintar karya Tere Liye. Penelitian ini bersifat deskriptif kualitatif. Teknik pengumpulan data menggunakan teknik simak, baca, dan catat. Teknik analisis data menggunakan triangulasi teori. Berdasarkan hasil analisis menunjukkan bahwa dalam novel Si Anak Pintar terdapat nilai pendidikan antikorupsi kejujuran yang meliputi: (1) tidak mencuri, (2) tidak memalsukan dokumen, (3) melaksanakan kebijakan berdasarkan kebenaran, (4) bersaing  secara sehat, dan (5) tidak menggelapkan dana. Sementara pada novel Negeri Para Bedebah terdapat kontradiksi nilai pendidikan antikorupsi kejujuran yang meliputi: (1) tidak melaksanakan kebijakan ber-dasarkan kebenaran, (2) kolusi, (3) penyuapan, (4) memalsukan dokumen, dan (5) melakukan penipuan. Temuan-temuan tersebut relevan sebagai bahan ajar pendidikan antikorupsi. Kata kunci: nilai, pendidikan, antikorupsi, novel, sosiologi sastra